2014
DOI: 10.1002/ente.201300119
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of the Formation of Surface Palladium Carbide during the Catalytic Combustion of Lean Methane/Air Mixtures

Abstract: The catalytic combustion of <1 % methane in air over palladium‐based catalysts is investigated. The influence of operating parameters and pretreatment conditions on the activity and stability of the catalysts is studied. X‐ray photoelectron spectroscopy analysis of Pd/Al2O3 indicates the emergence of Pd carbide, even under lean conditions (0.6 % methane) and at temperatures as low as 180 °C. Significant differences were observed in the light‐off temperatures and extent of coke deposition, depending on whether … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 34 publications
5
8
0
Order By: Relevance
“…The formation of the Pd n+ in reduced Pd catalysts was also observed in other studies [33,34]. When the XPS profiles of the used catalysts at different times on stream were deconvoluted, a new phase appeared around 336.1-335.5 eV ( Figures 5 and 6), which can be attributed to PdCx, according to the NIST database and Setiawan et al [35] who identified the formation of this specie at a binding energy of the Pd3d5/2 peak at around 335.9 eV. As can be seen in Table 3, the proportion of PdCx phase mainly rose during the first 5 h of reaction, though a slight increase is observed up to 40 h. Beyond this time the amount remains constant.…”
Section: Characterization Resultssupporting
confidence: 81%
“…The formation of the Pd n+ in reduced Pd catalysts was also observed in other studies [33,34]. When the XPS profiles of the used catalysts at different times on stream were deconvoluted, a new phase appeared around 336.1-335.5 eV ( Figures 5 and 6), which can be attributed to PdCx, according to the NIST database and Setiawan et al [35] who identified the formation of this specie at a binding energy of the Pd3d5/2 peak at around 335.9 eV. As can be seen in Table 3, the proportion of PdCx phase mainly rose during the first 5 h of reaction, though a slight increase is observed up to 40 h. Beyond this time the amount remains constant.…”
Section: Characterization Resultssupporting
confidence: 81%
“…22 This particle size estimation agrees with what has been observed with TEM analysis, where particle sizes were measured to vary between 6 and 13 nm. 22 The influence of water vapour adsorption on the active site and the support was investigated using TPD analysis. The intensity of water desorbed from the support material (γ-δ-Al 2 O 3 ) and 1.2 wt% Pd/Al 2 O 3 catalysts are plotted in Figure 6(a) for fresh active catalyst and 6(b) for the used catalyst (7 hours at 320 o C).…”
Section: Figsupporting
confidence: 90%
“…Thed etailed kinetic reaction mechanism (23 steps) of methaneo naPt catalytic surface was adopted, [24] which includes six adsorption elementary reactions,e leven surface chemistry elementary reactions,a nd six desorption elementary reactions. Nineg aseous components (CH 4 [25,26],i ti ss een that these mechanisms apply well to the simulation of catalytic methanec ombustion.…”
Section: Modeling Approach Physicalmodel and Control Equationmentioning
confidence: 98%